Textile finishing using polymer nanocomposites for radiation shielding, flame retardancy and mechanical strength - Gowri, Sorna; Khan, Mohammad Akram; Srivastava, Avanish Kumar (2021)
The uses of nanotechnologies in textiles are strategic and allow textiles to become multifunctional. There is an ever-increasing demand for new functionalities, like flame retardancy, radiation shielding, improved mechanical strength etc., for highly specific applications. There is no industrial supply for the above-mentioned functionalities. Keeping in view of this background, surface treatment becomes one of the most important methods to create new textile properties. Polymer nanocomposites based on coatings for textiles have a huge potential for innovative modifications of surface properties like flame retardancy, radiation shielding and improved mechanical properties, which can be applied with a comparatively low technical effort and at moderate temperatures. This review compiles recent research on polymer nanocomposites for functional finishing of textiles to understand the theoretical and experimental tools on polymer nanocomposites and their applications in textiles.
Bibliografija: 152 jed.
Abstract.
Keywords: Tekstili -- Završna obrada -- Polimerni nanokompoziti -- Zaštita od zračenja -- Otpornost na vatru -- Mehanička čvrstoća